Analisis Kemampuan Pemahaman Konsep Matematika Ditinjau Dari Penggunaan Multimedia Game Petualangan Dalam Limas Berbasis Mobile Learning di SMP Negeri 1 Tilango - Nadila Nurfariza Tahir; Sumarno Ismail; Franky Alfrits Oroh; Perry Zakaria; Kartin Usman (Universitas Negeri Gorontalo, 2022)
This study aims to describe the student’s ability to understand the mathematical concept using adventure game multimedia mobile learning based on the pyramid (PDL) in Grade VIII. This study is qualitative descriptive. The subjects are 40 students of grade VIII which is reduced to 6 students to take the preliminary test of the ability to understand the concept and the interview process seen from the results of the students’ preliminary test. Data collection technique includes preliminary tests, interviews, documentation, and observation. The data analysis applies reduction, data presentation, and conclusion. The results based on interviews conducted with students and teachers show that students’ conceptual abilities vary widely, where some achieve high abilities, medium abilities, and low abilities. It is also seen from the learning process that the use of adventure game multimedia in the pyramid helps to give its vibes to a more interesting learning process.